Lands and peoples. The world in color. Volume 6 : Canada, the United States - Merrick, Helen Hynson
The arctic -- American indians -- Canada -- The atlantic provinces -- Quebec -- The western provinces -- Canadian cities -- Yukon and northwest territories -- The United States -- The northeastern states -- The southern states -- North central states -- Mountain and pacific states -- Alaska and Hawaii -- United States cities -- United States parks -- Canada's parks